Diseño de un sistema de conservación in situ para el cantón Gonzanamá - Romero Ortega, Ángel Rafael (2014)
The protection system of the city look for the integration of the forests and the nature protection areas (FNPA) existing and other forms of conservation, it tries to join between public person and private, who have knowledge and be able in environmental topics to develop activities of protection in important ecosystem zones. The population of the Canton is 12716 and its population density habitants y is 1822 hab/km2; through the study we identify 4 protected areas under the category of (FNPA) : Colambo – Yacury, Santa Rita, La Chorera y Rosabel – La Chora and 3 forest areas, that cover the 13,30% of the Canton’s surface ; the units of covered nature are the pastureland (nature grass 29,92 % , pasture 7,49 %) that cover the 37,47% of the surface; There are 7 types of ecosystem where stand out the thicket andean montano xerico with 26,06% ; it could identify 2 potential zones that for its richest in flora and fauna and two micro basins that should protect for its importance. Finally we proposing the composition and the structure of the cantonal conservation system that allow Strengthening the plans and programs defined in the municipal and parish organization.